Structural Analysis for Identification of Key Factors of Sustainable Regional Development Rice Farming - Samodra Laya, Willie; Fauzi, Akhmad; M Kolopaking, Lala; Mulatsih, Sri (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2025)
The sustainability of rice farming as a strategic commodity is determined by many factors that have different roles. This study aims to present a structural analysis as an instrument for identifying and classification factors that affect the Sustainable Regional Development Rice Farming in the present and future perspectives using the Matrix of Cross Impact Analysis (MICMAC) method. From the analysis, it is known that the factors from the institutional dimension and the technological dimension have the most influence in achieving results in the present and the future. These factors are 1) policy regulations at the national, provincial, and district/city levels; 2) digital transformation/agriculture 5.0; 3) development of social and technological innovation; 4) transformation and institutional collaboration; 5) availability of agricultural infrastructure and facilities in rice fields; 6) the rate of adoption of innovation and technology by farmers; and 7) farmers who are members of farmer groups. Meanwhile, the factors with a very high dependence are factors from the social dimension and the economic dimension. The factor of productivity of paddy fields per year has a very high dependence on the present, while it will increase the welfare of farmers in the future. The results of this structural analysis can be used as input in the development of a road map for the availability and price stability of rice and improve the sustainable welfare of rice farmers.